Comparison of the relationship between cerebral white matter and grey matter in normal dogs and dogs with lateral ventricular enlargement - Schmidt, Martin J.; Laubner, Steffi; Kolecka, Malgorzata; Failing, Klaus; Moritz, Andreas; Kramer, Martin; Ondreka, Nele; Justus Liebig University Giessen (My University, 2015)
Large cerebral ventricles are a frequent finding in brains of dogs with brachycephalic skull conformation, in comparison with mesaticephalic dogs. It remains unclear whether oversized ventricles represent a normal variant or a pathological condition in brachycephalic dogs. There is a distinct relationship between white matter and grey matter in the cerebrum of all eutherian mammals. The aim of this study was to determine if this physiological proportion between white matter and grey matter of the forebrain still exists in brachycephalic dogs with oversized ventricles. The relative cerebral grey matter, white matter and cerebrospinal fluid volume in dogs were determined based on magnetic-resonance-imaging datasets using graphical software. In an analysis of covariance (ANCOVA) using body mass as the covariate, the adjusted means of the brain tissue volumes of two groups of dogs were compared. Group 1 included 37 mesaticephalic dogs of different sizes with no apparent changes in brain morphology, and subjectively normal ventricle size. Group 2 included 35 brachycephalic dogs in which subjectively enlarged cerebral ventricles were noted as an incidental finding in their magnetic-resonance-imaging examination. Whereas no significant different adjusted means of the grey matter could be determined, the group of brachycephalic dogs had significantly larger adjusted means of lateral cerebral ventricles and significantly less adjusted means of relative white matter volume. This indicates that brachycephalic dogs with subjective ventriculomegaly have less white matter, as expected based on their body weight and cerebral volume. Our study suggests that ventriculomegaly in brachycephalic dogs is not a normal variant of ventricular volume. Based on the changes in the relative proportion of WM and CSF volume, and the unchanged GM proportions in dogs with ventriculomegaly, we rather suggest that distension of the lateral ventricles might be the underlying cause of pressure related periventricular loss of white matter tissue, as occurs in internal hydrocephalus.
Keywords: ddc:630